Pembelajaran Gender pada Anak Usia Dini Melaui Pendekatan Sentra - Eliyyil Akbar (Yinyang: Jurnal Studi Islam Gender dan Anak, 2016)
Abstract: The trend of viewing a woman as a figure whose task is to assist a man by referring to religious doctrines represents its textual paradigm. Due to accepting the doctrines without considering the context of its emergence, there are many men who show their discriminative attitude and behavior. As a result, the justice that is expected and struggled by women in various ways not come to a reality. Considering this condition, it is necessery to introduce gender equality to children in their early childhood to minimize gender-based injustice. This kind of intoduction should be done not only theoritacally, but also in real practices. This paper describes central approach gender learning. Gender learning may affect to all aspects of child development such as cognitive, social and emotional, moral and motoric aspects. Learning process applying the pay much attention to their needs, and give them an understanding that men an women have equal rights. Teaching gender to young children means promoting gender equality to the society. Keywords: leraning, gender, central method